Organic Synthesis of TiO2 Nanoparticles For Object Detection Application - Priya, Hari; polasi, P. Phani Kumar; E. Jayapriya,; kumar, B.P.Pradeep (International Journal of Psychosocial Rehabilitation, 2020)
Nanotechnology is a piece of science and innovation about the control of the issue on the nuclear and atomic scale - this implies things that are around 100 nanometers over. Nanotechnology incorporates making items that utilization parts this little, for example, electronic gadgets, impetuses, sensors, and so forth.Nowadays eco-friendly synthesized metal oxide (TiO2 NPs) nanoparticles were playing various roles in the application field of electronics. Here, TiO2 NPs are synthesized by utilizingAdathodavasicaleaves. Further the synthesized metal oxide nanoparticles were subjected to various characterization techniques for morphological studies.Nanomaterial behave differently as the size changes with respect to the bulk. It is necessary to characterize physical, structural and optical properties of a material to qualify as nanomaterial.In generalNanotechnology is used in many communications, computing and electronic applications,it provides faster, smaller and more portable systems. These systems can manage and store larger and larger amounts of information. Finally, an application on electronics i.e., object detection is done.